Optimization of duration of the chartering period on the basis of time charter - Судник, Надежда Витальевна (Technology audit and production reserves, 2015)
The practice of chartering was not based on theoretical grounds to establish the chartering term due to the lack of thereof. Accordingly, the proposed solution of problems related to improving the efficiency of management of time charter vessels by optimizing the chartering term to reflect changes in market conditions of freight market and attract a variety of purposes of chartering tonnage. The first statement of the problem involves the use of a time-charter ships to perform a specific transport operation. In such case the tenants - carriers base on the fact that during the period of chartering would be able to fully ensure the entire volume of the planned transportation of cargo using freight market conjuncture with minimum risk. The second statement of the problem involves maximizing profits of tenant, projected on the basis of the trend of the freight market conditions. Presented methodological approaches allow reasonably determine the duration of the chartering period for the time charter, thereby reducing the impact of commercial risks time charter transaction participants; and also allows to link the duration of the terms of the time charter with a capacity of transport work that they will be performed.